Breeding habitat suitability modeling of white-rumped vulture (Gyps bengalensis, Gmelin JF, 1788) in proximity to vulture restaurants in central lowland of Nepal - Baral, Nishan; Joshi, Suraj; Rai, Nitant; Joshi, Ankit Bilash; Poudel, Kiran; Yadav, Shailendra Kumar (Frontiers in Conservation Science, 2025)
Nepal has a total of nine species of vultures. White-rumped vulture, Gyps bengalensis, is distributed throughout South Asian countries. It is mostly confined to tropical and sub-tropical regions. South Asian countries have recorded a decline of more than 97% of three resident species, including the white-rumped vulture, since the mid-1990s. The study focused on predicting the breeding habitat suitability of white-rumped vultures in the Nawalparasi East and Rupandehi districts in the central lowland of Nepal, where vulture restaurants have been operating. The site visit for the study was conducted in December–January 2021. A total of 52 nests were recorded in the study area. Using the MaxEnt approach, the generated model resulted in a mean area under the curve (AUC) of 0.950 with a standard deviation of 0.011 and a true skill statistics (TSS) value of 0.8207, indicating good model robustness. The average of the 10 models’ “maximum test sensitivity plus specificity Cloglog threshold” value was 0.5784. Using this, a binary map was produced, and it was found that 96.88 km2 (3.82%) of the total of 2,532 km2 area was suitable breeding habitat for the white-rumped vulture. The categorical variable land use–land cover (LULC), with category “forest” with positive correlation and category “agricultural land” with negative correlation, had the highest contribution in the model building, with 50.5% contribution, so it was the most important variable for breeding habitat selection by white-rumped vulture. It was followed by biome with category “tropical subtropical grassland, savannas, and shrubland” with 21.8% and Euclidean distance from water source with 12.8% as other top contributors. The contribution of forest was attributed to the presence of suitable trees for nesting and the absence of carcasses in the open field due to the tradition of burying dead cattle, which was suggested to be the reason for the negative correlation based on various studies. Furthermore, easy detectability of carcasses in grassland and savanna, appropriate humidity for hatching of eggs, and depositing carcasses near water bodies were suggested to be major reasons for the contribution of these variables based on reviewed literature and research works. Based on these results, the study recommended that vulture management sectors focus on the management of these variables, prioritizing accordingly to conserve the white-rumped vulture.